New dean to helm SMU Lee Kong Chian School of Business: SMU appoints Professor Gerard George as new business school dean from 2015 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
The Singapore Management University (SMU) has appointed Professor Gerard George from the Imperial College London as Dean of the SMU Lee Kong Chian School of Business from 1 January 2015 for a five-year term. A Professor of Innovation and Entrepreneurship, Professor Gerard George is currently Deputy Dean of Imperial College Business School and the Director of the Rajiv Gandhi Centre. The Centre facilitates Imperial College London's strategic commitments in India for joint research initiatives and educational programmes in innovation and entrepreneurship. He also serves as the International Dean of BML Munjal University, an innovative new university mentored by Imperial and located near New Delhi.